Simplify the equation x^2 - 8x + 16 = 0 to obtain the value of x.
![\begin{gathered} x^2-8x+16=0 \\ x^2-2\cdot4\cdot x+(4)^2=0 \\ (x-4)^2=0 \\ (x-4)(x-4)=0 \\ x=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/upwsm5yvmjpd8kafw669990g44x0s3n335.png)
Equation has one solution, x = 4.
Simplify the equation x ( x - 1 ) = 8 to obtain the value of x.
![\begin{gathered} x(x-1)=8 \\ x^2-x-8=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u67ylfxgdzpmzsa0grc19iqzo47bghtwuu.png)
This is a quadratic equation which is not a perfect square so it has two solutions.
Simplify the equation x^2 = 16 to obtain the value of x.
![\begin{gathered} x^2=16 \\ x=\sqrt[]{16} \\ =\pm4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/maqz1pq1koxef27a6jo6cajcjrnim9heek.png)
Thes equation has two solution x = 4 and x = -4.
So equation x^2 - 8x + 16 = 0 has only one solution and remaining equation has two solutions.